Pharmacokinetics and Safety of a Single Oral Dose of Peficitinib (ASP015K) in Japanese Subjects With Normal and Impaired Hepatic Function - Miyatake, Daisuke; Shibata, Tomohisa; Toyoshima, Junko; Kaneko, Yuichiro; Oda, Kazuo; Nishimura, Tetsuya; Katashima, Masataka; Sakaki, Masashi; Inoue, Kazuaki; Ito, Takayoshi; Uchida, Naoki; Furihata, Kenichi; et al. (Clinical pharmacology in drug development, 2020)
Peficitinib (ASP015K) is a novel Janus kinase inhibitor developed for the treatment of rheumatoid arthritis (RA). The impact of hepatic impairment on the peficitinib pharmacokinetic (PK) and safety profile was investigated in non‐RA subjects (n = 24) in an open‐label, parallel‐group, multicenter comparative study in Japan. Subjects received a single, clinically relevant, oral dose of a peficitinib 150 mg tablet under fasting conditions. Plasma PK parameters were measured for peficitinib and its metabolites H1 (sulfate and methylated metabolite), H2 (sulfate metabolite), and H4 (methylated metabolite) in subjects with normal hepatic function, mild hepatic impairment, or moderate hepatic impairment. The peficitinib area under the plasma‐concentration–time curve from time 0 to infinity (AUCinf) and maximum observed concentration (Cmax) were not markedly different in subjects with mild hepatic impairment versus normal hepatic function. In subjects with moderate hepatic impairment versus normal hepatic function, the geometric mean ratios for peficitinib AUCinf and Cmax, were 1.92 (90% CI: 1.39, 2.66) and 1.82 (90% CI: 1.24, 2.69), respectively. Five treatment‐emergent adverse events (TEAEs) were experienced by 3 subjects, 1 in each group. There were no deaths, no serious TEAEs, and no TEAEs leading to withdrawal. In summary, the PK profile was unaltered in subjects with mild hepatic impairment after a single clinically relevant dose of peficitinib, but exposure almost doubled in subjects with moderate hepatic impairment. Peficitinib dose reduction may be considered in RA patients with moderate hepatic impairment.